Schistosoma mansoni venom allergen-like protein 6 (SmVAL6) maintains tegumental barrier function. Issue 4 (March 2021) - Perally, Samirah; Geyer, Kathrin K.; Farani, Priscila S.G.; Chalmers, Iain W.; Fernandez-Fuentes, Narcis; Maskell, Daniel R.; Hulme, Benjamin J.; Forde-Thomas, Josephine; Phillips, Dylan; Farias, Leonardo P.; Collins, James J.; Hoffmann, Karl F.
Graphical abstract: Highlights: Smval6 is expressed in oral/ventral suckers, oesophageal gland and mesenchymal cells of Schistosoma mansoni . Smval6 knockdown increases surface membrane permeability. SmVAL6 interacts with Sm14 and DLC proteins. Abstract: The Schistosoma mansoni venom allergen-like protein (SmVAL) superfamily is a collection of at least 29 molecules that have been classified into two distinctive groups (Group 1 and Group 2 SmVALs). The fundamental basis for SmVAL segregation relates to signal peptide and conserved cysteine retention (present in all Group 1 SmVALs, but absent in all Group 2 SmVALs). These structural differences have led to the hypothesis that most Group 1 SmVALs, found as components of schistosome excretory/secretory (E/S) products, predominantly interact with their environment (intermediate or definitive hosts) whereas the Group 2 SmVALs are retained within the schistosome to fulfil parasite-related functions. While experimental evidence to support Group 1 SmVAL/host interactions is growing, similar support for identification of parasite-related Group 2 SmVAL functions is currently lacking. By applying a combination of approaches to the study of SmVAL6, we provide the first known evidence for an essential function of a Group 2 SmVAL in schistosome biology. After whole mount in situ hybridisation (WISH) localised Smval6 to the anterior region of the oesophageal gland (AOG) and cells scattered through the mesenchyme in adult schistosomes, short interfering RNA (siRNA)-mediated silencing of Smval6 was employed to assess loss of function phenotypes. Here, si Smval6- mediated knockdown of transcript and protein levels led to an increase in tegumental permeability as assessed by the quantification of TAMRA-labelled dextran throughout sub-tegumental cells/tissues. Yeast two hybrid screening using SmVAL6 as a bait revealed Sm14 (a fatty acid binding protein) and a dynein light chain (DLC) as directly interacting partners. Interrogation of single-cell RNA-seq (scRNA-seq) data supported these protein interactions by demonstrating the spatial co-expression of Smval6 / dlc / Sm14 in a small proportion of adult cell types (e.g. neurons, tegumental cells and neoblasts). In silico modelling of SmVAL6 with Sm14 and DLC provided evidence that opposing faces of SmVAL6 were likely responsible for these protein/protein interactions. Our results suggest that SmVAL6 participates in oesophageal biology, formation of higher order protein complexes and maintenance of tegumental barrier function. Further studies of other Group 2 SmVALs may reveal additional functions of this enigmatic superfamily.